Latecomers to Trade-Union Democracy: The Emergence, Growth, and Role of Union Stewards in the National Union of Public Employees. Issue 40 (September 2019) - Fryer, R. H. (Bob); Williams, Stephen
Abstract : This paper situates the emergence of union stewards in the National Union of Public Employees (NUPE) within the union's history and an analysis of workplace representation and its implications for trade-union organization, mobilization, and democracy. Union stewards were distinctive, being located in the union's branches in rule. Their development reflected a huge shift in the orientation of NUPE's national leadership and occurred in the context of major reorganizations of local government, the NHS, and water industry from 1972 to 1974; the introduction (or rejection) of incentive pay schemes; and NUPE's involvement in large national disputes, which highlighted the weaknesses of relying on the traditional role of the union's full-time officials and branch secretaries. While the paper suggests the inappropriateness and inapplicability of a one-dimensional account of an inherent antagonism between union stewards, as representatives of NUPE's rank-and-file members, and the 'bureaucracy' of the union's full-time officials, it represents only the beginnings of an assessment of the limits and possibilities of democracy in unions.